Platelet Distribution Amplitude (PDW) and Mean Platelet Volume (MPV): two simple, practical and specific indicators of platelet activation in Liquid PRF - Crisci, Michela; Lepore, Giovanni; Crisci, Francesco; Feleppa, Federica; Crisci, Alessandro; Flagiello, Fabiana (Archives of Clinical and Biomedical Research, 2025)
Background: platelet indices are potentially useful markers in diagnosing liquid PRF platelet activation and its quality. An increase both in mean platelet volume (MPV) and platelet distribution width (PDW) is due to platelet activation and comes from platelet enlargement and pseudopodia formation. Our hypothesis is that, using different vials and centrifuges to obtain liquid PRF, there might be different MPV and PDW values, which would point toward different type or level of activation. Methods: Platelet indices (MPV, PDW, MPV/Plt, PDW/Plt) were measured in different Liquid PRF types/groups. Five different types of Liquid PRF were prepared: Liquid Fibrinogen 2700 rpm × 3’ (820 g) (RCF clot=608 g; RCF max =816 g; RCF min =326 g); i-PRF 3300 rpm (1220 g) × 3’(RCF clot =765 g; RCF max = 1008 g; RCF min =403 g); i-PRF 700 rpm (55 g) × 5’(RCF clot =38 g; RCF max =55 g; RCF min =22 g); A-PRF 1300 rpm (189 g) × 5’(RCFclot=142 g; RCFmax=189 g; RCFmin=66 g); C-PRF 2500 rpm (700 g) × 8’ and also PRP (Platelet rich Plasma) [2200 rpm, (1147 g) x 20 min]. The studied hematological parameters were: platelet count (Plt), mean platelet volume (MPV) and platelet distribution width (PDW), as well as MPV/Plt ratio and PDW/Plt ratio. Results: the highest MPV found in Vacumed FL vials was of 9.428±0.69 fL, while in original S- PRF vials it was 9.56±0.77 fL p=0.49, whatever the type of centrifuge employed; highest PDW found in Vacumed FL vials was of 11.71±0.66 %, while with original S-PRF vials it was 11.7±1.95 % p=0.974, whatever the type of centrifuge employed. Hence no difference tied to the type of vial and centrifuge was found between obtained values, but only based on the type of Liquid PRF produced. Conclusions: PDW and MPV are the most specific markers for platelet activation, as they do not increase in values during simple platelet enlargement and their value is not related to the type of vial and centrifuge used, but only to the type of PRF produced.